Evaluación de la semilla de Theobroma cacao L, CCN51, de la provincia de Ramón Castilla en obtención de licor y manteca de cacao - Vela Mozombite, Emmanuel de Jesús (2020)
This research was mostly carried out in the Province of Ramon Castilla – Caballo cocha, in the populated center of San pedro de palo seco, from where the raw material (cocoa as cob) was harvested, then it was transferred to the production center of pedigree, in Caballo cocha, to start the process of obtaining dry grains, for which the process was followed: selection/ breaking of the cob, heavy, pre-drained, fermentation, pre-drying, drying, removal and Stored. First the fruits were controlled, the cobs were seen and performed the size of the cobs, pH controls (average 4.02 – 4.69) and brix degrees (average 16.2), of the mucilage, then the fermentation was controlled (lasts 4 days), as well as the average pH of the cotyledon. (who it varies from 5.94 and descends to 4.70), all this deposited on wooden drawers, then came the drying which takes place inside a shed, with transparent polycarboanto roof, stirring every 30 minutes, the temperature which reaches about 41.9o C,being a total of 5 days, and obtain if a grain with a humidity of 6.30% (dry base). The process of obtaining liqueur and cocoa butter was as follows: cocoa beans, selection, classification, cleaning, roasting, heavy, husked, crushed, cocoa liqueur pressure (280)/extraction and cocoa butter, one of the very important steps is the roasting of the grain, being the ideal temperature and time: 120or C by 45 ', after this step the control of moisture, fats and total proteins was carried out, complying with the requirement. Next, it went to the crusher where the cocoa liqueur is obtained which had a yield of 67.5 - 70.0%, finally, it was subjected to a press to obtain butter, having a yield of 32.5 – 30.0%, with respect to the cocoa bea.